Application of microdosed intravenous omeprazole to determine hepatic CYP2C19 activity - Mahmoudi, Mazyar; Foerster, Kathrin; Burhenne, Jürgen; Weiß, Johanna; Mikus, Gerd; Haefeli, Walter E. (Journal of clinical pharmacology, 2021)
Omeprazole is an established probe drug to assess cytochrome P450 (CYP) 2C19 activity (phenotyping). Because it has nonlinear pharmacokinetics (PK) after oral administration (autoinhibition of metabolism), the true impact of coadministered perpetrators on CYP2C19 substrates might be underestimated after regular doses. We tested the dose linearity of an intravenous omeprazole microdose of 100 µg and compared it with a 20-mg dose in 4 healthy poor metabolizers (PMs) and 6 extensive metabolizers (EMs) of CYP2C19 in the presence and absence of a strong inhibitor (voriconazole). Without voriconazole, omeprazole exposure was dose-proportional irrespective of the genotype, but in PMs geometric mean ratios (GMRs) of AUC0-∞ were 6.6-fold higher and molar metabolic ratios of 5-OH omeprazole/omeprazole approximately 10-fold lower. Voriconazole increased omeprazole exposure in EMs approximately 5-fold (AUC0-4 GMR after 100 µg omeprazole, 4.61; 90% confidence interval [CI], 2.69-7.89; AUC0-4 GMR after 20 mg omeprazole, 5.5; 90%CI, 1.07-1.46), whereas no clinically significant impact on PK in PMs was observed (GMR AUC0-4 after 100 µg omeprazole, 1.29; 90%CI, 0.81-2.04; GMR AUC0-4 after 20 mg omeprazole, 1.25; 90%CI, 1.07-1.46). Linear regression and Bland-Altman analyses revealed excellent agreement between AUC0-∞ and AUC0-4 of omeprazole (r2 = 0.987; bias, 0.35%; 95%CI, −3.197% to 3.89%) and also the molar metabolic ratio, 5-OH omeprazole/omeprazole (r2 = 0.987; bias, −3.939; 95%CI, −9.06% to −1.18%), suggesting that an abbreviated sampling protocol can be used for intravenous CYP2C19 phenotyping and drug interaction studies. In conclusion, the PK of intravenous omeprazole microdoses closely reflects the changes observed with regular omeprazole doses; however, to avoid autoinhibition of probe drugs, microdosing appears to be the favorable technique.